2015
DOI: 10.17344/acsi.2014.1262
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of a Sensitive HPLC–PDA Method for Simultaneous Determination of Torasemide and Spironolactone in Human Plasma using Central Composite Design

Abstract: A sensitive, accurate, precise and rapid HPLC-PDA method was developed and validated for the simultaneous determination of torasemide and spironolactone in human plasma using Design of experiments. Central composite design was used to optimize the method using content of acetonitrile, concentration of buffer and pH of mobile phase as independent variables, while the retention factor of spironolactone, resolution between torasemide and phenobarbitone; and retention time of phenobarbitone were chosen as dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…A detailed comparison of methods for the determination of torasemide in human biological samples is showed in Table 8 . The developed method of the study is more sensitive than all other methods developed for determination of torasemide as a single analyte in human plasma [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . In addition, the proposed method uses less plasma (200 μL) than many other reported methods, and has better human compliance for volunteers in bioequivalence and pharmacokinetic studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed comparison of methods for the determination of torasemide in human biological samples is showed in Table 8 . The developed method of the study is more sensitive than all other methods developed for determination of torasemide as a single analyte in human plasma [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . In addition, the proposed method uses less plasma (200 μL) than many other reported methods, and has better human compliance for volunteers in bioequivalence and pharmacokinetic studies.…”
Section: Resultsmentioning
confidence: 99%
“…A rapid, sensitive and reliable determination of torasemide in human plasma is essential to evaluating its pharmacokinetics in clinical trials and bioequivalence researches. Several methods have been reported including gas chromatography–tandem mass spectrography (GC–MS) [9] , capillary zone electrophoresis (CZE) [10] , high-performance liquid chromatography–tandem ultraviolet detection (HPLC–UV) [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] and high-performance liquid chromatography–tandem electrochemical detection (HPLC–ED) [20] , [21] , [22] to determine the concentration of torasemide as a single analyte [9] , [12] , [18] , [19] , [20] , [21] or in combination with its important metabolites [10] , [11] , [13] , [14] , [15] , [16] or with other diuretic drugs [23] , [24] in plasma [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] or other biological samples [9] , [13] , [20] , [21] , [22] , [23] , [24] . Barroso et al [9] applied GC–MS to determine the concentration of torasemide in human urine, which needs complicated preparation for derivatization and is not suitable for bioequivalence studies of large quantity of samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several analytical methods have been reported by HPLC for the quantification of furosemide, torasemide, azosemide, bumetanide, or etacrynic acid either alone or in combination with other drugs, both in their prescribed forms and in biological fluids [9][10][11][12][13][14][15][16][17][18][19][20][21]. The abovementioned methods, however, have not been employed for the simultaneous quantification of the five LDs in any pharmaceutical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that several analytical methods are developed for TOR and SPI individually and combined dosage forms. HPLC [7][8][9][10][11][12] ,HPTLC 13, and UV 14 method have been developed for TOR and SPI in pharmaceutical dosage form. To best of our knowledge UV simultaneous equation method have been reported for estimation of TOR and SPI in combined dosage form.…”
Section: Introductionmentioning
confidence: 99%